Proteomics, bioinformatics and targeted gene expression analysis reveals up-regulation of cochlin and identifies other potential biomarkers in the mouse model for deafness in usher syndrome type 1F - Chance, Mark R. (Oxford University Press, 2010)
Proteins and protein networks associated with cochlear pathogenesis in the Ames waltzer (av) mouse, a model for deafness in Usher syndrome 1F (USH1F), were identified. Cochlear protein from wild-type and av mice at postnatal day 30, a time point in which cochlear pathology is well established, was analyzed by quantitative 2D gel electrophoresis followed by mass spectrometry (MS). The analytic gel resolved 2270 spots; 69 spots showed significant changes in intensity in the av cochlea compared with the control. The cochlin protein was identified in 20 peptide spots, most of which were up-regulated, while a few were down-regulated. Analysis of MS sequence data showed that, in the av cochlea, a set of full-length isoforms of cochlin was up-regulated, while isoforms missing the N-terminal FCH/LCCL domain were down-regulated. Protein interaction network analysis of all differentially expressed proteins was performed with Metacore software. That analysis revealed a number of statistically significant candidate protein networks predicted to be altered in the affected cochlea. Quantitative PCR (qPCR) analysis of select candidates from the proteomic and bioinformatic investigations showed up-regulation of Coch mRNA and those of p53, Brn3a and Nrf2, transcription factors linked to stress response and survival. Increased mRNA of Brn3a and Nrf2 has previously been associated with increased expression of cochlin in human glaucomatous trabecular meshwork. Our report strongly suggests that increased level of cochlin is an important etiologic factor leading to the degeneration of cochlear neuroepithelia in the USH1F model.